Pengaruh Implementasi Kegiatan keagamaan (Pembinaan, Pembiasaan, Pendidikan), Terhadap Peningkatan Semangat Ibadah Siswa - Destya Melya Sari; Hilmi Hilmi; Madyan Madyan; Aprizal Wahyudi Diprata (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2023)
This article discusses and analyzes the Effects of the Implementation of Religious Activities (Coaching, Habituation, Education), on Increasing Student Worship Enthusiasm, as additional insight for teachers and prospective teachers so they can understand what affects Increasing Student Worship Enthusiasm. Writing this Literature Review article uses library research methods sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of this article are: 1) Guidance has an effect on Increasing the Spirit of Worship of Students; 2) Habits Affect the Improvement of Students' Worship Enthusiasm; and 3) Education has an effect on increasing the spirit of student worship. In addition to these 3 exogenous variables that affect endogenous variables in increasing the spirit of worship, there are many other factors including training, reward values, and the school environment.